Importancia de la situación de la mujer para la nutrición infantil en los países en desarrollo - Smith, Lisa C.; Ramakrishnan, Usha; Ndiaye, Aida; Haddad, Lawrence J.; Martorell, Reynaldo (International Food Policy Research Institute, 2004)
Malnutrition affects one out of every three pre-school-age children living in developing countries. This disturbing, yet preventable, state of affairs causes untold suffering and, given its wide scale, presents a major obstacle to the development process. Volumes have been written about the causes of child malnutrition and the means of reducing it. But the role of women’s social status in determining their children’s nutritional health has gone largely unnoticed until recently. This study explores the relationship between women’s status and children’s nutrition in three developing regions: South Asia, Sub-Saharan Africa (SSA), and Latin America and the Caribbean (LAC).... This research shows unequivocally that making a decision at the policy level to improve women’s status produces significant benefits. Not only does a woman’s own nutritional status improve, but so too does the nutritional status of her young children. Raising women’s status today is a powerful force for improving the health, longevity, mental and physical capacity, and productivity of the next generation of young adults." -- from text of Abstract.